2018
DOI: 10.1186/s12909-018-1312-1
|View full text |Cite
|
Sign up to set email alerts
|

Medical students create multiple-choice questions for learning in pathology education: a pilot study

Abstract: BackgroundMedical students facing high-stakes exams want study resources that have a direct relationship with their assessments. At the same time, they need to develop the skills to think analytically about complex clinical problems. Multiple-choice questions (MCQs) are widely used in medical education and can promote surface learning strategies, but creating MCQs requires both in-depth content knowledge and sophisticated analytical thinking. Therefore, we piloted an MCQ-writing task in which students develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 40 publications
2
50
3
3
Order By: Relevance
“…Students reported that their appreciation for well-written MCQs grew and their perceived approaches to MCQs were altered as a result of this study, which has not been previously reported. Our finding that students perceived question-writing to benefit their learning stands in contrast to previous reports which suggest that the minority of medical students find question-writing to be beneficial as a learning strategy [16,18,30]. This discrepancy may be explained in part due to the in-depth training medical students received on how to write MCQs in our study, improving understanding and appreciation for the writing process.…”
Section: Question Partcontrasting
confidence: 99%
“…Students reported that their appreciation for well-written MCQs grew and their perceived approaches to MCQs were altered as a result of this study, which has not been previously reported. Our finding that students perceived question-writing to benefit their learning stands in contrast to previous reports which suggest that the minority of medical students find question-writing to be beneficial as a learning strategy [16,18,30]. This discrepancy may be explained in part due to the in-depth training medical students received on how to write MCQs in our study, improving understanding and appreciation for the writing process.…”
Section: Question Partcontrasting
confidence: 99%
“…MCQ writing for question banks has also been reported as a small group learning activity for medical students, who report this as an enjoyable and useful learning activity (Gooi and Sommerfeld, 2015;Harris et al, 2015;Lawrence, Famokunwa and Ziff, 2016). However MCQ writing may be less efficient than other learning methods (Kurtz et al, 2019) and have high cognitive load for students (Grainger et al, 2018). Our pilot of an MCQ authoring and answering exercise had variable student acceptance (Grainger et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…However MCQ writing may be less efficient than other learning methods (Kurtz et al, 2019) and have high cognitive load for students (Grainger et al, 2018). Our pilot of an MCQ authoring and answering exercise had variable student acceptance (Grainger et al, 2018). We now report three consecutive yearlong case studies of a student-generated MCQ learning exercise that aimed to enhance deep learning and knowledge construction in a 4 th year pathology course and reflect on the lessons learnt.…”
Section: Introductionmentioning
confidence: 95%
“…PeerWise is a free online multiple choice question (MCQ) repository linked to educational institutions that provides a platform for creation, assessment and review of MCQ . Studies conducted in students have suggested that PeerWise may increase academic performance through increased engagement with the writing to learn process . The writing to learn process is thought to increase knowledge through increased content exposure and repetition as well as organisation and self‐evaluation …”
Section: Introductionmentioning
confidence: 99%
“…8 Studies conducted in students have suggested that PeerWise may increase academic performance through increased engagement with the writing to learn process. 9 The writing to learn process is thought to increase knowledge through increased content exposure and repetition as well as organisation and self-evaluation. 10,11 In addition to the numerous modes of delivery of CME, there are many factors which influence the effectiveness of CME in increasing knowledge and improving physician outcomes.…”
Section: Introductionmentioning
confidence: 99%